PENGGUNAAN BAHAN ADDITIVE ANTI STRIPPING AGENT TERHADAP KEAWETAN CAMPURAN LATASTON (HRS-WC) - ., Sawaluddin; Widodo, Slamet; Sulandari, Eti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
This study aims to determine the level of durability mixture lataston with added material additives Anti Stripping Agent, comparing mixture lataston with and without additives Anti Stripping Agent, as well as determine the effect of the use of additives Anti Stripping Agent on the characteristics of the mixture lataston according to the General Specifications of Highways in 2010. comparisons are made on the condition KAO. The results show the value of stability of 0.1% (1190 Kg) 0.2% (1213 Kg), 0.3% (1235 Kg), 0.4% (1224 Kg), 0.5% (1179 Kg), from the fifth variation is taken 0.3% (1235 Kg) which has the highest stability values. Lataston mix of characteristics (HRS-WC) with extra additive anti-stripping agent, stability increased by 5.64% from 1247 kg, flow increased by 1.02% from 2.267 mm, Marshall Quotient also increased by 4.80% from 383, 00 kg / mm, density, and VFB increased by 0.069% from 2.286 g / cm3, and 0.16% from 72.076%, while the VIM and VMA tended to decrease by 0.70% from 5.152% and 0.37% from 19.854% , The effect of the additive anti-stripping agent on the level of durability or durability of a mixture Lataston (HRS-WC) made in this study was originally amounted to 90.30% and then increased to 91.29%, which means an increase of 1.09%. Â  Keywords: Anti Stripping Agent, Level of durability, Marshall Test.